2010
DOI: 10.1186/1471-2172-11-37
|View full text |Cite
|
Sign up to set email alerts
|

Differential and coordinated expression of defensins and cytokines by gingival epithelial cells and dendritic cells in response to oral bacteria

Abstract: BackgroundEpithelial cells and dendritic cells (DCs) both initiate and contribute to innate immune responses to bacteria. However, much less is known about the coordinated regulation of innate immune responses between GECs and immune cells, particularly DCs in the oral cavity. The present study was conducted to investigate whether their responses are coordinated and are bacteria-specific in the oral cavity.ResultsThe β-defensin antimicrobial peptides hBD1, hBD2 and hBD3 were expressed by immature DCs as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 53 publications
2
52
0
2
Order By: Relevance
“…With the bacterial invasion, β-defensins stimulate the secretion of chemokines, such as IL-8 and MCP-1, from dendritic cells, and, also, act as chemoattractants, which bring phagocytes and lymphocytes to the site of infection. Correspondingly, the activated immune response limits innate response and, hence, secretion of β-defensins (42) . Our findings were in agreement with previous studies shown that smoking downregulates hβD-2 expression (37,39,43) .…”
Section: According To Fan Et Al (2015)mentioning
confidence: 99%
“…With the bacterial invasion, β-defensins stimulate the secretion of chemokines, such as IL-8 and MCP-1, from dendritic cells, and, also, act as chemoattractants, which bring phagocytes and lymphocytes to the site of infection. Correspondingly, the activated immune response limits innate response and, hence, secretion of β-defensins (42) . Our findings were in agreement with previous studies shown that smoking downregulates hβD-2 expression (37,39,43) .…”
Section: According To Fan Et Al (2015)mentioning
confidence: 99%
“…Like in the other human body regions, the expression of HBD-1 in the oral mucosa cells occurs constantly. The basal HBD-2 concentration in the oral epithelium is relatively low, but increases rapidly in the presence of cytokines (TNF-α and IL-1β), bacteria (Fusobacterium nucleatum, Porphyromonas gingivalis) and fungi (Candida albicans) [12,18,20,28]. In the non-oral epithelium the HBD-2 expression occurs only in the case of inflammation or infection.…”
Section: The Expression and The Role Of Defensins In The Oral Cavitymentioning
confidence: 99%
“…Cytokines and chemokines are involved in the interaction between gum epithelial cell and dendritic cells (DCs). The responses are bacterio-specific differential and coordinated regulation between gingival EC and DCs may be important in regulation of innate hemostasis and responses to pathogens in the oral cavity [1]. Polymorph nuclear cell induce protective type TH1 cytokines epithelial response in an in-vitro model of oral candidiasis [16].…”
Section: Specific Immunity Il2il4il15mentioning
confidence: 99%
“…Among these influences epithelial cell produced cytokines and chemokines [1]. The aim of the present mini-review is confined onto the oral epithelial cytokines.…”
Section: Introductionmentioning
confidence: 99%